The development of house prices in London - Svoboda, David (2017)
The subject of this bachelor thesis is to analyze London residential housing market in the period of time from 1995 to 2016. In the first part of the thesis the emphasis is put on the definition of theories related to the topic. It includes the reasons why house prices are worth measuring. Another point of the theory are the economic fundaments which influence the house prices. The main topic and result of this bachelor thesis is a deep analysis of the development of house prices in London. Based on the analysis, in the conclusion, it is enabled to evaluate the stability of the market. It is particularly the problematics of high house prices and affordabulity, which is solved in this document. These topics have become increasingly popular in London, recently. The work concentrates data from many fields, which affect developments housing markets, in one document. Thanks to it, the work provides comprehensibly processed data from statistical authorities such as HM Land Registry or Office for National Statistics including useful comparisons of important fundamentals.